2018
DOI: 10.1080/1057610x.2018.1445501
|View full text |Cite
|
Sign up to set email alerts
|

Terrorist Decision Making in the Context of Risk, Attack Planning, and Attack Commission

Abstract: Terrorists from a wide array of ideological influences and organizational structures consider security and risk on a continuous and rational basis. The rationality of terrorism has been long noted of course but studies tended to focus on organizational reasoning behind the strategic turn toward violence. A more recent shift within the literature has examined rational behaviors that underpin the actual tactical commission of a terrorist offense. This article is interested in answering the following questions: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…This result suggests that there is some assessment of risk by the offenders, and that they are selecting targets rationally. This is consistent with the findings of Gill et al (2018), who concluded that fear of detection plays a strong role in the decision-making encompassing a terrorist event by those groups not intending the offender's death at the scene of the attack. It can be proposed that there may be differences between targets relevant to ideology and realistic targets with increased chance of success.…”
Section: Discussionsupporting
confidence: 92%
“…This result suggests that there is some assessment of risk by the offenders, and that they are selecting targets rationally. This is consistent with the findings of Gill et al (2018), who concluded that fear of detection plays a strong role in the decision-making encompassing a terrorist event by those groups not intending the offender's death at the scene of the attack. It can be proposed that there may be differences between targets relevant to ideology and realistic targets with increased chance of success.…”
Section: Discussionsupporting
confidence: 92%
“…In regards to a backlash of terrorist attacks in Israel following indiscriminate state repression, for instance, our results suggest that security officials should assess state and civilian targets within local jurisdictions that are vulnerable to retaliatory attacks during this critical period following the engagement of harsh counterterrorism measures with the populace. Based on a situational prevention framework to reduce opportunities for attacks on targets (Boba, 2009; Clarke & Newman, 2006; Gill et al., 2017; Gill, Marchment, Corner, & Bouhana, 2020; Morris, 2015), an analysis of target qualities most germane to a backlash of attacks against the state and its citizens (e.g., iconic stature, proximity to terrorist's operational base, and the amount or density of people) may help inform prioritization and resource allocations for safeguarding particular targets in the wake of indiscriminate repressive counterterrorism actions.…”
Section: Discussionmentioning
confidence: 99%
“…Biographies in various forms have been used to understand criminality, such as for female offenders (Carlen 1985), and the lives of prisoners (Morgan 1999). In terrorist research the analysis of biographies has produced findings on recruitment processes, and motivations (Shapiro and Siegel 2012;Teymur 2007;Gill et al, 2018). Although there are many limitations to auto/biographies, which are discussed later, the current method "can only hope to provide a more in-depth level of insight into men's lives as criminals" (Goodey 2000, p.494).…”
Section: Datamentioning
confidence: 99%